1991
DOI: 10.5144/0256-4947.1991.322
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection in Pregnancy

Abstract: , midstream urine specimens were collected during the first antenatal visit of 2,642 pregnant patients. The specimens were obtained for the purpose of microbiological study. Significant bacteriuria was found in 15.8% (N = 419); 188 of the patients were asymptomatic and 231 were symptomatic, yielding an incidence of 7.1% and 8.7%, respectively. Two hundred females with negative urine cultures were selected as a control group, and matched by age, gravidity, and gestational age. The frequency of occurrence of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…coli has been identified as the most common pathogen isolated among the pregnant women in this study (Fig. 1), which was consistent with the majority of the reported studies in literature [13][14][15][16][17][18][19][22][23][24]27,28] . However, E. coli formed 53% of the isolated organisms, which is lower than what have been reported in countries (Table 2) such as Pakistan, 2006 (78.6%) [19] ; Turkey, 2005 (77%) [16] ; Iran, 2009 (70%) [24] and in UAE, 2005 (66.7%) [17] .…”
Section: 77%supporting
confidence: 89%
See 1 more Smart Citation
“…coli has been identified as the most common pathogen isolated among the pregnant women in this study (Fig. 1), which was consistent with the majority of the reported studies in literature [13][14][15][16][17][18][19][22][23][24]27,28] . However, E. coli formed 53% of the isolated organisms, which is lower than what have been reported in countries (Table 2) such as Pakistan, 2006 (78.6%) [19] ; Turkey, 2005 (77%) [16] ; Iran, 2009 (70%) [24] and in UAE, 2005 (66.7%) [17] .…”
Section: 77%supporting
confidence: 89%
“…This rate is much lower than the previously reported from Saudi Arabia; 14.2% bacteriuria in pregnant women from the eastern region (in 1989), where only 25% of the women were symptomatic (i.e., the prevalence of ASB was 10.5%). 15.8% bacteriuria was reported in 1991 from the Western region, where the ASB was 7.1% [27][28] . Furthermore, our prevalence rate was much lower than the recent reports from other Middle Eastern countries.…”
Section: Discussionmentioning
confidence: 98%
“…The hormonal changes in pregnancy leads to decreased bladder tone, diminished peristalsis and dilatation of renal pelvis and ureter 16,17 It has been claimed that pregnancy produces physical obstruction in the female urinary tract and obstruction is one of the important risk factor for the development of the infection. 18,19 Diabetics are at higher risk of urinary tract infection due to the unfavourable metabolic changes such as elevated blood sugar levels, which suppress the immune system. In our study 10% UTI patients were diabetics, similar findings was found in study by Ramzan M.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies have been retrospective and descriptive in nature . Most studies have tried to raise awareness of the emergence of antimicrobial resistance, but many of the data available are outdated [16,22,23,25,26,31,[39][40][41][42][43][44]. Hence, periodic updates are needed to track this emergence.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no review papers have been published on this matter in KSA. This review is important as it will increase awareness of UTIs and antimicrobial resistance patterns in KSA [40,[42][43][44] As antimicrobial susceptibility patterns change rapidly, new resistant strains are emerging. Our review focused on the most common pathogens and their antibiotic susceptibility patterns.…”
Section: Introductionmentioning
confidence: 99%